Mengkaji Sumber, Penggunaan Dana, dan Dampak Likuiditas terhadap PT. Akbar Indo Makmur Stimec Tbk. - Nelma Husni; Himyar Pasrizal (Universitas Nusantara PGRI Kediri, 2026)
The purpose of this study is to determine the sources of funding and their effect on the liquidity of PT. Akbar Indo Makmur Stimec Tbk in 2022–2023. This study uses a quantitative descriptive approach, the population is PT. Akbar Makmur Stimec Tbk for the period 2022-2023, with data analysis techniques using descriptive analysis. There is no comparison or correlation between these variables and other factors. The results of the study show that by looking at the sources and uses of cash to measure liquidity, businesses can earn 16.53% in 2022 and 0.27% in 2023. Findings from examining the sources and uses of cash reports indicate that the level of liquidity of PT. Akbar Makmur Stimec Tbk increases when cash increases, and decreases when cash decreases.